Technology evolution for silicon nano-electronics selected, peer reviewed papers from the proceedings of the International Symposium on Technology Evolution for Silicon Nano-Electronics 2010, June 3-5, 2010, Tokyo Institute of Technology, Tokyo, Japan - Miyazaki, Seiichi; Tabata, Hitoshi (Trans Tech Publications, 2011)
Silicon ultra-large scale integrated circuits (ULSIs) are now faced with various physical limits to further scaling. Therefore, it is very important to establish the fundamental science and technology required to produce nano-scale complementary metal-oxide-semiconductor devices (Nano-CMOS) having high performance, new functionalities and larger-scale integration. The scope of this book covers: - Nano-scale complementary metal-oxide-semiconductor devices (Nano-CMOS), - Novel functional devices, materials, and nanoprocessing technologies, - Nano-bio physics and technologies for future nano devices, - Variability control technologies and Signal integrity. This makes it a very useful handbook on the subject. Review from Book News Inc.: The 38 selected and peer-reviews papers gathered here explore possible directions now that silicon-based semiconductors are running up against physical limits to further miniaturization. They cover nano-structure physics and nano-material science, nano-processing and nano-devices, nano-system functionality integration, and nano-device integrity for variability and fluctuation and management and integration. Among the topics are photoluminescence characteristics of ultra-thin silicon-on-insulators at low temperature, the nano-surface modification of silicon with an ultra-short pulse laser process, the microscopic structure of directly bonded silicon substrates, and analyzing threshold voltage variations in fin field effect transistors.
Keywords: Nanoelectronics -- Congresses.; Nanostructured materials -- Congresses.; Metal oxide semiconductors -- Congresses.; elektronické knihy; electronic books